SERVICES IN BUSINESS AVIATION (Perner's Contacts, 2017)
The main aim of this article is to analyse services in one department of Business Aviation Company and try to think how to improve attractiveness for the client. The paper focuses on general description of services in Business Aviation and on top of that it offers definition of services of Operational Control Centre. Last chapter of the paper describes various weaknesses of the services provided by the aircraft operator. The paper reveals some interesting facts about business aviation.
Keywords: Business Aviation; Operational Control Centre; Customer Services